Synthesis and Characterization Catalyst γ-Al2O3 and Al/γ-Al2O3 using XRD Analysis - Selpiana Selpiana; David Bahrin; RR Yunita Bayu Ningsih; Aditia H Akbar; Ayu Permatasari (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2022)
Catalysts have an essential role in chemical processes because they can control reactions and produce the desired product. In general, catalysts function to speed up chemical reactions that can take place by lowering the activation energy. By decreasing the activation energy, the minimum energy required for the collision is reduced so that the reaction can occur faster. Selection of the suitable material to be used as a catalyst is an effort that must be made to achieve a successful process and obtain cost efficiency. The choice of material as metal and support was the aim of this research. Aluminum (Al) was the material chosen as metal and γ-Al2O as the support. The method used in the synthesis of this catalyst was dry impregnation. It is hoped that more metal will stick to the support. In this study, catalyst synthesis was carried out with two variations of treatment. The first treatment was using Al as metal and γ-Al2O3 as the support. The second treatment did not use metal only γ-Al2O3 as the support. The resulting material was characterized by XRD analysis. The analysis found that in the diffractogram pattern of Al /γ-Al2O3, the peaks appeared at 2θ = 37o; 46o and 67o. The impregnation process went well. Aluminum was evenly distributed (sticks) to the pore surface of the support and entered the poresKeywords: Catalyst, metal-support, Al/γ-Al2O3, dry impregnation, XRD